Salmonella – At Home in the Host Cell - Malik Kale, Preeti; Jolly, Carrie E.; Lathrop, Stephanie; Winfree, Seth; Luterbach, Courtney; Steele-Mortimer, Olivia (Frontiers in Microbiology, 2011)
The Gram-negative bacterium Salmonella enterica has developed an array of sophisticated tools to manipulate the host cell and establish an intracellular niche, for successful propagation as a facultative intracellular pathogen. While Salmonella exerts diverse effects on its host cell, only the cell biology of the classic “trigger”-mediated invasion process and the subsequent development of the Salmonella-containing vacuole have been investigated extensively. These processes are dependent on cohorts of effector proteins translocated into host cells by two type III secretion systems (T3SS), although T3SS-independent mechanisms of entry may be important for invasion of certain host cell-types. Recent studies into the intracellular lifestyle of Salmonella have provided new insights into the mechanisms used by this pathogen to modulate its intracellular environment. Here we discuss current knowledge of Salmonella-host interactions including invasion and establishment of an intracellular niche within the host.